Inkjet-Printed Flexible MEMS Switches for Phased-Array Antennas - Mahmuda Akter Monne; Xing Lan; Chunbo Zhang; Maggie Yihong Chen (International Journal of Antennas and Propagation)
This paper presents a fully inkjet-printed flexible MEMS switch for phased-array antennas. The physical structure of the printed MEMS switch consists of an anchor with a clamp-clamp beam, a sacrificial layer, and bottom transmission lines. 5-mil Kapton® polyimide film is used as a flexible substrate material. Two different types of conductive ink PEDOT : PSS from Sigma Aldrich and silver nanoparticle ink from NovaCentrix are used for the fabrication of different printed layers. Layer-by-layer fabrication process and material evaluation are illustrated. Layer characterization is done with respect to critical thickness and resistance using 2D/3D material analysis. Fujifilm Dimatix Material Printer (DMP-2800) is used for fabrication, and KLA-Tencor (P-7) profiler is used for 2D and 3D analysis of each layer. The MEMS switch has a low actuation voltage of 1.2 V, current capacity of 0.2195 mA, a current on-off ratio of 2195 : 1, and an RF insertion loss of 5 dB up to 13.5 GHz. Printed MEMS switch technology is a promising candidate for flexible and reconfigurable phased-array antennas and other radio frequency (RF) and microwave frequency applications.